2012
DOI: 10.1056/nejmoa1110734
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Abdominal CT for Evaluating Suspected Appendicitis

Abstract: Low-dose CT was noninferior to standard-dose CT with respect to negative appendectomy rates in young adults with suspected appendicitis. (Funded by GE Healthcare Medical Diagnostics and others; ClinicalTrials.gov number, NCT00913380.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
208
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 278 publications
(230 citation statements)
references
References 38 publications
(29 reference statements)
11
208
1
4
Order By: Relevance
“…Many studies have shown the value of CTS in evaluation of acute abdominal pain with sensitivity of 90-100%, specificity of 91-99%, accuracies of 94-98%, PPVs of 92-98%, and NPVs of 95-100% for diagnosing AA. [12][13][14] Our results were similar to those published in literature with an overall diagnostic accuracy of 92.6%. Recent trend toward medical management of early AA will make CTS a mandatory diagnostic test for all patients with clinical suspicion of the diagnosis.…”
supporting
confidence: 89%
“…Many studies have shown the value of CTS in evaluation of acute abdominal pain with sensitivity of 90-100%, specificity of 91-99%, accuracies of 94-98%, PPVs of 92-98%, and NPVs of 95-100% for diagnosing AA. [12][13][14] Our results were similar to those published in literature with an overall diagnostic accuracy of 92.6%. Recent trend toward medical management of early AA will make CTS a mandatory diagnostic test for all patients with clinical suspicion of the diagnosis.…”
supporting
confidence: 89%
“…The authors came to the conclusion that low-dose CT is equally suitable for diagnosing appendicitis. For example, Kim et al determined the rates of unnecessary appendectomies in 890 patients after standarddose CT and low-dose CT in a randomized prospective study and compared the results [21]. The patients were divided into two groups.…”
Section: Resultsmentioning
confidence: 99%
“…A recent report by Kim, et al [21] concluded that low-dose abdominal CT was not inferior to standard-dose CT regarding NAR in young adults, with a lower median radiation dose -length product as compared to standard-dose CT (116 mGy * cm vs. 521 mGy * cm, respectively).…”
Section: Disclosurementioning
confidence: 98%
“…If US is inconclusive, we may consider low-dose CT a possible radiological examination in the diagnosis of acute appendicitis [21,22]. With regard to pediatric patients, US is the first choice imaging technique.…”
Section: Disclosurementioning
confidence: 99%